The influence of multiculturalism in the architecture of Lima - Langschwager Angulo, Ariana (Universidad de Lima. Carrera de Arquitectura, 2019)
The explosive migration of people from around the world to Peru resulted in the fusion of several cultures and styles. As a consequence, the district of Rímac presents different types of constructions ranging from those that survived the colonial era to those built in the hillsides, which reflect the values and needs of the communities that dwell there. However, there are not parameters to tell us which architecture is better or worse. Living in such a multicultural city as Lima makes us think that this urban reality is the result of expressions from different places that, due to various circumstances and history itself, have met in our city.